THERAPEUTIC PATIENT EDUCATION AND COUNSELLING IN GERIATRIC ONCOLOGY - Villars, H.; Champarnaud, M.; Balardy, L.; Nourhashemi, F. (Innovation in aging, 2017)
Therapeutic patient education (TPE) has largely demonstrated its efficiency in the care of patients suffering from chronic conditions, as defined by the World Health Organization (WHO). At the same time TPE has been implemented in Oncology, particularly in the field of pain management but not only, considering cancer as a ‘chronic condition’. Moreover, in the early 2000s, Geriatric Oncology has begun to emerge as a discipline. Indeed, as the incidence of cancer regularly increases during the life, cancerous pathologies are prevalent in subjects over 65 years, and the care of these subjects is raising very different issues and challenges from those of younger patients (polypathology and co-morbidity, iatrogenesis, cognitive disorders and dementia, sensory deficits, role of caregivers...).TPE has secondary followed this development in getting adjusted to the specific needs of this population. Because of its global, multidimensional and holistic character, TPE now appears as an interesting tool in Geriatric Oncology. Some educational programs have been created, implemented and evaluated but only a few are specifically addressed to the geriatric population. This communication is a brief review of Therapeutic Education Programs designed for geriatric patients suffering from cancer and hematological conditions.